Angularly Selective Enhanced Vortex Screening in Extremely Layered Superconductors with Tilted Columnar Defects - Gonzalo Rumi; Vincent Mosser; Marcin Konczykowski; Yanina Fasano (Condensed Matter)
We report on two mechanisms of angularly selective enhanced screening in the solid vortex phase of extremely layered superconductors with tilted columnar defects (CDs). We study Bi2Sr2CaCu2O8+δ samples with different densities of CD tilted 45° from the c-axis, and conduct local ac Hall magnetometry measurements, probing the sustainable current of the vortex system. We reveal two types of maxima in sustainable current for particular directions, detected as dips in the magnetic transmittivity of the vortex system. First, for a smaller number of vortices than of defects, an enhancement of screening is detected at an angular location <semantics><msubsup>Θdip1</msubsup></semantics>∼45° for H applied close to the direction of CD. For a larger number of vortices than of CD, <semantics><msubsup>Θdip1</msubsup></semantics> decreases towards the <semantics>ab</semantics>-plane direction upon warming. Second, a pair of additional dips in transmittivity are detected at angles <semantics><msubsup>Θdip2</msubsup></semantics> closer to, and quite symmetric with, the <semantics>ab</semantics>-plane. These two types of angularly selective enhanced screening reveal the effective pinning by tilted CD even for the composite vortex lattices nucleated in tilted fields in Bi2Sr2CaCu2O8+δ.